Skeletal Effects of Early-Life Exposure to Soy Isoflavones—A Review of Evidence From Rodent Models - Chin, Kok-Yong; Pang, Kok-Lun (Frontiers in Pediatrics, 2020)
Isoflavones are dietary phytoestrogens commonly found in soy-based products. The widespread presence of isoflavones in soy infant formula and breast milk may have long-lasting effects on the development of sex-hormone sensitive organs, like the skeleton. Animal early-life programming models are suitable for testing the skeletal effects of pre- and neonatal exposure of soy isoflavones. This review aims to collate the impacts of early-life exposure of soy isoflavones as evidenced in animal models. The isoflavones previously studied include daidzein, genistein or the combination of both. They were administered to rodent pups during the first few days postnatal, but prolonged exposure had also been studied. The skeletal effects were observed when the animals reached sexual maturity or after castration to induce bone loss. In general, neonatal exposure to soy isoflavones exerted beneficial effects on the skeletal system of female rodents, but the effects on male rodents seem to depend on the time of exposure and require further examinations. It might also protect the animals against bone loss due to ovariectomy at adulthood but not upon orchidectomy. The potential benefits of isoflavones on the skeletal system should be interpreted together with its non-skeletal effects in the assessment of its safety and impacts.